Clinical case of treatment of septic defect of bone and soft tissues of the lower leg - Baida , Maxim; Rushay , Anatoliy; Martynchuk , Oleksandr (The Ukrainian Scientific Medical Youth Journal, 2024)
the clinical case is an example of complex reconstruction of septic defect of the tibia tissues, the main principles of which were the reduction of traumatic interventions, the choice of optimal multistage tactics; adequate medication. The soft tissue defect was closed with a rotational sural flap, and the bone defect was replaced with a distraction regenerate with the subsequent use of a semi-rigid system of fixation Softcast-Skotchkast; the data of the EFI and Karlstrom-Olerud external fixation index scales with regard to the complexity of the case according to NUSS objectively confirm this.